Tingkat Pertumbuhan Anakan Sengon di Lahan Bekas Terbakar pada Kebun Penelitian dan Percobaan Universitas Muhammadiyah Palangkaraya - Ise Afitah (Anterior Jurnal, 2013)
Wood Sengon (Paraserianthes falcataria) is a versatile timber for light construction, crafts, cigar boxes, veneer, plywood, matches, musical instruments and pulp. Sengon planted as shade trees, ornamental plants, and reforestation. The problems that faced the burnt peat is related to determining the appropriate type of soil acidic and resistant to non periodic inundation. Besides it takes a special kind of seeds, peat forest encountered many obstacles such as puddles, accessibility and prone to burning. From the observations during the three-month field observations obtained an average height increase in the amount Sengon of 11,46 cm tillers. This indicates a high level of each plant is very significant compared to the increase in diameter and number of leaves of plants, which is respectively 0.88 and 1.57 mm strands.